Muslims in France: clash of culture Muslims immigrants - Ahmad Razimi, Mohd Shahril (IDOSI Publications, 2017)
The aim of this paper is to review the French society and it impact on the Islamic culture, more precise the impact on the Islamic principle. This document highlights issues that Muslim immigrant or resident face.France has seen a significant shift in its society, from big empire to one colonize country by the German and were the society was a mix of origin people and immigrant from the colonized countries .this shift of power lead to multi-cultural society with rang of diversity especially in the 1960. However, this cultural diversity poses some challenges on Muslims based on differing needs and expectations. The Muslim community faces big challenge to adapt in France, this occur to the people have experiences to live there and deal with French society.For Muslim involve in the society they must refer to the principles of their faith and based on the Islam principle.The purpose of this papers to highlighted the importance of having strategies that identify the needs and expectations of the cultural diverse citizen. This paper aim to investigate and illustrate the culture and the clash of culture in French society. The finding and the work it cannot be general for the western culture due to many deferential polices and system and background of the society .in other word this paper addressing the French society and all the institution under French.